THE ADAPTATION PROCESS OF BREAST CANCER WOMEN - Londoño Calle, Yenly Catherine (Investigación y Educación en Enfermería, 2009)
Objective: discover the process of adaptation to their new life conditions and state of health within a sociocultural context. Methodology: qualitative study supported in the Founded Theory by means of in depth interviews to a sample of twenty resident women who received treatment for breast cancer in the city of Medellín, Colombia from 2005 to 2007. Results: the reach of the analysis allowed establishing a conceptual order, showing a process of adaptation in four stages, denominated thus: 1. Discovering the disease, 2. Accepting the disease, 3. Overcoming disease, and 4. Adapting to a new body and a new life. Conclusions: the adaptation of the breast cancer women with breast cancer is a complex process because they must face continuously the multiple imbalances that affect their emotional, physical, mental and social dimensions